Determinants of the loan loss allowance: some cross-country comparisons - Iftekhar Hasan; Larry D. Wall (Bank of Finland, 2003)
This paper analyses the determinants of banks loan loss allowances for samples of US banks and three non-US samples: a group of 21 countries, Canada and Japan.The model includes fundamental (or non-discretionary) determinants of the allowance such as non-performing loans, and discretionary determinants such as income before the loan loss provision.The results suggest that the loan loss allowance is sensitive to pre-provision income in almost all samples.However, the results also suggest that some variables thought to reflect fundamental factors in US analysis, such as net chargeoffs, are not significant factors for non-US banks.
URN:NBN:fi:bof-20140807224
Keywords: G21; G28; E58; F23; G33; 330; loan loss allowance; accounting standards; international banking; nonperforming loan; discretionary accruals